Effects of moist‐ and dry‐heat cooking on the meat quality, microstructure and sensory characteristics of native chicken meat. (25th August 2017) - Chumngoen, Wanwisa; Chen, Chih‐Feng; Tan, Fa‐Jui
Abstract: This study investigates the effects of moist‐ (water‐cooking; WC) and dry‐heat (oven‐cooking; OC) on the quality, microstructure and sensory characteristics of native chicken breast meat. The results revealed that OC meat had a significantly higher cooking time, cooking loss, and shear force values and lower L* values. Protein solubility decreased after cooking in both cooking methods; however, no statistical difference was observed between WC and OC meats, whereas collagen solubility and myofibrillar fragmentation index (MFI) increased after cooking and WC meat exhibited higher collagen solubility and MFI ( P  <   0.05). The fiber diameter and sarcomere length decreased substantially after cooking, and fibril shrinkage was noticeable in OC meat ( P  <   0.05). Descriptive sensory analysis revealed that WC meat exhibited a significantly higher moisture release and lower initial hardness, chewdown hardness and residual loose particles. A darker color and enhanced chickeny flavor were observed for OC meat. Based on the unique sensory and physicochemical characteristics in demand, producers should employ appropriate cooking methods to optimize native chicken meat quality.